A guide to Hodgkin and non-Hodgkin lymphomas: similarities and differences. (23rd September 2021) - Holdsworth, Fiona; Worku, Dominic; Bretton, Alanna le; Vella, Claire; Walker, Emma
Abstract : In the extraordinary times the COVID-19 pandemic has created for cancer patients and the health professionals caring for them, the need for strong knowledge and understanding of disease processes and treatments has never been more important. This article presents a review of Hodgkin lymphoma and non-Hodgkin lymphoma. These two common haematology diagnoses are frequently suspected by GPs and non-cancer professionals, and subsequently treated by haematologists and chemotherapy outpatient departments across the country. It is therefore important for all health professionals, including nurses in all settings, to be aware of the main characteristics of both of these lymphomas. There are strong similarities and striking differences between the disease processes, the presenting symptoms, prognostics and treatment pathways. The age of presentation in each is markedly different. There is a significant contrast in the number of subtypes between the two diagnoses, but the presenting symptoms are similar as are investigations required for diagnoses.